2021
DOI: 10.1089/acm.2020.0455
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Ginkgolide Injection in the Treatment of Ischemic Stroke Based on a Randomized Clinical Trial

Abstract: Objective: To evaluate the long-term cost-effectiveness of ginkgolide plus aspirin compared with placebo plus aspirin treatment of ischemic stroke. Background: Stroke is the leading cause of death and long-term disability in China, with high incidence, high mortality, and heavy disease burden. In addition to Western medicines, Chinese clinical guidelines for diagnosis and treatment of acute ischemic stroke recommend application of Chinese patent medicines. Ginkgolide injection is commonly used in the clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…The cost of intravenous injections was obtained from the mean price of medical services in 12 provinces across China to represent the national medical service price level (i.e., Beijing, Shanghai, Jiangsu, and Zhejiang). The costs of recurrent stroke were derived from the published literature ( Xiang et al, 2021 ). All costs were discounted at 5% annually and inflated in 2021 Chinese Yuan 2020 using the medical care component of the consumer price index ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The cost of intravenous injections was obtained from the mean price of medical services in 12 provinces across China to represent the national medical service price level (i.e., Beijing, Shanghai, Jiangsu, and Zhejiang). The costs of recurrent stroke were derived from the published literature ( Xiang et al, 2021 ). All costs were discounted at 5% annually and inflated in 2021 Chinese Yuan 2020 using the medical care component of the consumer price index ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Ginkgo diterpene lactone meglumine injection is one of the monomer injections that have been approved for marketing, which includes effective ingredients of ginkgolides A, B, and K with advantages of high content of active ingredients and low adverse reactions ( Zhou et al, 2017 ). Additionally, previous studies have demonstrated that ginkgolide injection and ginkgolide B can protect against IS as well ( Nabavi et al, 2015 ; Xiang et al, 2021 ). In this meta-analysis, we further found that clinical efficacy of ginkgo terpene lactone injections (especially ginkgo diterpene lactone meglumine injection) was superior to that of other drugs in the treatment of IS including ginkgo leaf extract and dipyridamole injection and Shuxuening injection.…”
Section: Discussionmentioning
confidence: 96%
“…Besides, G. biloba diterpene lactone meglumine injection (referred to GB injection in this study), extracted from G. biloba containing over 50% GB and other diterpene lactones, was chosen as a positive control. The therapeutic effect of this injection plus aspirin has also been clinically validated for vascular recanalization and neuron recovery after stroke [14] .…”
Section: Introductionmentioning
confidence: 99%